Cognitive Behaviour Therapy for Eating Disorders - Cooper, Z; Shafran, R (2008)
The eating disorders provide one of the strongest indications for cognitive behaviour therapy (CBT). This bold claim arises from two sources: first, the fact that eating disorders are essentially cognitive disorders and second, the demonstrated effectiveness of CBT in the treatment of bulimia nervosa, which has led to the widespread acceptance that CBT is the treatment of choice. In this paper the cognitive behavioural approach to the understanding and treatment of eating disorders will be described. A brief summary of the evidence for this account and of the data supporting the efficacy and effectiveness of this form of treatment will be provided. Challenges for the future development and dissemination of the treatment will be identified. © 2008 British Association for Behavioural and Cognitive Psychotherapies.